Environmental Engineering Innovation to Tackle Water Crisis in Modern Era - Yuanyuan Wang; Shanshan Xu; Morse Kathryn (Journal of Moeslim Research Technik, 2024)
Water crisis has become one of the major challenges of the modern era, with increasing demand for clean water and decreasing availability of quality water resources. In this context, environmental engineering innovations are crucial to effectively address this challenge. This research aims to explore various environmental engineering innovations that can be used to address the water crisis in the modern era. The main focus of this research is to identify technical solutions that can be applied to improve water management and increase the availability of clean water. The research method used involved an in-depth literature survey to gather information on recent environmental engineering innovations in addressing the water crisis. In addition, the research also involved a comparative analysis of various solutions that have been implemented in different regions around the world. The results show that there are various environmental engineering innovations that can be effective in addressing the water crisis in the modern era, including water treatment technologies, sustainable water resource management, and the use of renewable energy in water treatment systems. The conclusion of this research is that environmental engineering innovations play an important role in addressing the water crisis in the modern era. By implementing these innovative solutions, it is expected to achieve water quality restoration and sustainable increase in clean water availability.